Optimasi Biaya Pengiriman Dimsum Dengan Metode Transportasi Pada UMKM Hoki Dimsum Ponorogo - Ukhriawati Mas'ula, Syevila; Naula Widiyawati, Eva; Putria Septerina Arisusilo, Melanie; Denny Pratama, Shepia; Purwaningrum, Titis (Teewan Journal Solutions, 2025)
UMKM Hoki Dimsum which is located at Jl. Sumoroto No 30, Kauman Ponorogo. In the distribution of Hoki Dimsum products, there were several obstacles, namely there was no recording or data collection, resulting in increased expenditure costs. The aim of this research is to optimize shipping costs. The results of research on the initial solution obtained for each NWC method Rp. 13,950, LC Rp. 10,500, and VAM Rp. 11,000. From each distribution with the minimum value, namely the Least Cost (LC) method. By using the three methods NWC, LC, VAM, a minimum cost value of IDR 10,500 is obtained. The routes resulting from the selected method are motorbike (A) to Balong and Mlarak, motorbike (B) to Balong, motorbike (C) to Kauman and Mlarak, motorbike (D) to Mlarak. distribution of dimsum products to Hoki Dimsum MSMEs gets optimal results. Least Cost (LC) is the most optimal method among the other two methods with the minimum cost of IDR 10,500/week.